Refocusing generalized myasthenia gravis: Patient burden, disease profiles, and the role of evolving therapy - Saccà, Francesco; Salort‐Campana, Emmanuelle; Jacob, Saiju; Cortés‐Vicente, Elena; Schneider‐Gold, Christiane (European journal of neurology, 2024)
Background and purpose Generalized myasthenia gravis (gMG) continues to present significant challenges for clinical management due to an unpredictable disease course, frequent disease fluctuations, and varying response to therapy. The recent availability of new pharmacologic therapies presents a valuable opportunity to reevaluate how this disease is classified, assessed, and managed and identify new ways to improve the clinical care of patients with gMG. Methods Narrative review was made of publications identified via searches of PubMed and selected congresses (January 2000–September 2022). Results New consensus definitions are required to ensure consistency, to better characterize patients, and to identify patients who will benefit from specific drugs and earlier use of these agents. There is a need for more frequent, standardized patient assessment to identify the cause of motor function deficits, provide a clearer picture of the disease burden and its impact on daily living and quality of life (QoL), and better support treatment decision‐making. Novel approaches that target different components of the immune system will play a role in more precise treatment of patients with gMG, alongside the development of new algorithms to guide individualized patient management. Conclusions gMG has a physical, mental, and social impact, resulting in a considerable burden of disease and substantially decreased QoL, despite standard treatments. The availability of novel, targeted treatments that influence key pathological mediators of gMG, together with new biomarkers, offers the potential to optimize patient management and ultimately enables a greater number of patients to achieve minimal manifestation status and a reduced burden of disease.